Narrow-pass-band filters based on binary superlattices with strong impedance contrast - Iakushev, D.A.; Makarov, N.M.; Pérez-Rodríguez, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The photonic band structure and transmission coefficient of a dielectric bilayer periodic array with strong impedance contrast are calculated and analyzed. It is found that the photonic band structure has broad pass bands and very narrow gaps. However, because of the strong impedance contrast and the use of lossless dielectric layers, the transmission spectrum exhibits sharp peaks inside the pass bands. The remarkable properties of the superlattice can be used for the fabrication of narrow-pass-band filters.